(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In recent times, due to the globalization the fashion of plant cultivation has been changing as well; imported, decorative acclimatized culinary herbs have been penetrating, therefore, new tasks to integrate them into the traditional plantations have been arising.The main aim of the paper is to select culinary herbs for the design solutions having different purpose and adapted to different environmental conditions, to reveal the possibilities to use the best properties of these plants, to help the persons interested in the use of culinary herbs to decide on the proper plant selection, to provide recommendations on the combination and composition possibilities of these plants.The authors of the article have analyzed and evaluated the research carried out in Lithuania related to the issues of culinary herb cultivation. In the Institute of Horticulture Lithuanian Research Centre for Agriculture and Forestry 24 species of culinary herbs are cultivated. By analyzing the culinary herbs cultivation technologies, plant bio ecology and morphology as well as priority propagation techniques have been evaluated; decorative properties of herbs and the possibility of their use in green plantations have been assessed.